Los conocimientos en el mercado - Ronan Le Velly; Frédéric Goulet; Alexandre Mallard (Revue d'anthropologie des connaissances)
Economic sociology does not ignore the question of knowledge when considering the way in which the drivers of economic action have been studied. A number of publications thus refer to a fundamental socio-cognitive issue: the interpretation of situations and the anticipation of the consequences of actions. Networks, culture, devices, institutions, institutions, entrepreneurs, competition and quality can be re-examined with regard to the issue of knowledge mobilization in the action that concerns them. Three themes are examined in depth here: uncertainty, problems linked to the absence or instability of knowledge in the definition of the quality of goods; the heterogeneity of regimes and types of knowledge mobilised in the valuation of goods; the performativity of economic knowledge in the case of the marketisation of the production of this knowledge.